2021
DOI: 10.3389/fendo.2020.610672
|View full text |Cite
|
Sign up to set email alerts
|

Immune System Effects of Insulin-Like Peptide 5 in a Mouse Model

Abstract: IntroductionInsulin-like peptide 5 (INSL5) is a peptide hormone with proposed actions in glucose homeostasis and appetite regulation via its cognate receptor, relaxin family peptide receptor 4 (RXFP4). Here, we look for evidence for their involvement in the immune system using a mouse model.MethodsIn silico analyses: we queried public databases for evidence of expression of INSL5-RXFP4 in immune system tissues/cells (NCBI’s SRA and GeoProfiles) and disorders (EMBO-EBI) and performed phylogenetic footprinting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Amongst gut endocrine cell products, insulin-like peptide 5 (INSL5) is confined to the distal large intestine, where it occurs in L-type enteroendocrine cells (EEC) that also contain glucagon-like peptide 1 (GLP-1) and peptide YY (PYY), both of these being costored with INSL5 in the same secretory vesicles of these EEC (Grosse et al 2014 ; Billing et al 2018 ; Vahkal et al 2021 ). The administration of an INSL5 mimetic and stimulation of hormone release from colonic L-cells using DREADD technology both cause defecation, but there is no evidence that either GLP-1 or PYY is involved in defecation control (Diwakarla et al 2020 ; Lewis et al 2020 ; Pustovit et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst gut endocrine cell products, insulin-like peptide 5 (INSL5) is confined to the distal large intestine, where it occurs in L-type enteroendocrine cells (EEC) that also contain glucagon-like peptide 1 (GLP-1) and peptide YY (PYY), both of these being costored with INSL5 in the same secretory vesicles of these EEC (Grosse et al 2014 ; Billing et al 2018 ; Vahkal et al 2021 ). The administration of an INSL5 mimetic and stimulation of hormone release from colonic L-cells using DREADD technology both cause defecation, but there is no evidence that either GLP-1 or PYY is involved in defecation control (Diwakarla et al 2020 ; Lewis et al 2020 ; Pustovit et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, they have never been reported to be directly related to CAD before, but some have been confirmed to affect the changes of immune targets in circulation. For example, INSL5, as a peptide hormone, after intraperitoneal injection, leads to significant changes in inflammatory factors such as IL-5, IL-7, M-CSF, IL-15 and IL-27 [ 43 ], and these inflammatory signals typically play a regulatory role in CAD. However, more direct evidence is needed to explore the causal relationship between them and CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Insl5 and Rxfp4 mRNA has been detected in the pancreas, thymus and in the gastrointestinal tract, 202,291 particularly in the L‐cells of distal gut 292–294 ; INSL5 has been shown to function as an orexigenic hormone, 291 and to influence colonic propulsion, 232,295 immune cell function, 296 and even human sperm motility 297 . Finally, a recent study identified a potential role for INSL5 (or relaxin‐3) signaling via ventral hypothalamic RXFP4 in the control of high‐fat and high‐protein diet consumption in mice 298 .…”
Section: Insulin‐like (Relaxin)‐family Peptide and Receptor Systemsmentioning
confidence: 99%